Stories About Truths and Euphemisms In the Political Arena: Unmasking Deception: The Power of Euphemisms in the Political Arena (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Politicians  are notorious for  their  employment  of  words  in  a  disguised  fashion  through the  usage of euphemisms. Consequently, their messagebecomes a recurrent theme of conspicuous deception. Electedgovernment representatives deliberately engage in grandiloquent expression consciousof its subversivecapacity. The deviancy of euphemisms is guided by socialnorms that politicians are permitted to exercise inorder tosafeguard their images. When politiciansenvelop seemingly good intentionswith consciousdeception,people are harmed  in  the process. Those in power  transgress  justice  and  commit  crimes  with their overwhelming command of euphemisms. In fact, euphemisms are utilized asmasks, hiding truths underthe protective tones of a speaker with a genuine, worthwhile goal. Selective vocabulary is employedto arouse,rationalize and justify. To achieve this end, politicians misrepresent the facts of various political situations by using terms  that completely  transform or  falsify  them.  Euphemisms are used simplistically in daily conversations. However, where they are used and misused more frequently is in the political arena, in such cases as “soft targets” or “peace keepers” or “collateral damage.” These expressions are heard frequently,while past ones are forgotten and new ones primed in their place as transgressions continue. In this paper, Iwill make useof Jurgen Habermas’public sphere theory,a critical theory that demonstrates how theaudience’s outlook affectspolitical action. Thisarticle will demonstrate the deliberate use ofeuphemisms in political language both as a cultural elementand as one that is constantly changing to suit the ever-changing politicalarena.